Repeated exposure to cutaneous high-frequency electrical stimulation prolongs the time course of secondary hyperalgesia: sensory processing - Lebrun, Louisien; Stouffs, Alexandre; Hermans, Emmanuel; van den Broeke, Emanuel N.; Leone, Caterina; Caspani, Ombretta; Truini, Andrea; Garcia-Larrea, Luis; Treede, Rolf-Detlef; Mouraux, André (Journal of neurophysiology, 2025)
Exposure to noxious stimuli induces secondary hyperalgesia (SH), likely due to long-term potentiation (LTP) in the dorsal horn or “central sensitization.” Previous studies have suggested that repeated exposure to a sensitizing stimulus may promote a persistent form of potentiation. We tested this hypothesis by characterizing the time course and spatial spread of SH induced by repeated exposures to high-frequency electrical stimulation (HFS) in healthy volunteers. Separate groups of 16 participants received either a single session of 5 or 10 HFS trains (“HFS 1x5” and “HFS 1x10” groups) or 2 sessions of 5 HFS trains separated by 1 hour and applied to the same forearm (“HFS 2x5” group) or the contralateral forearm (“HFS 2x5 bilateral” group). HFS trains consisted of 1 second of 100-Hz stimulation (×20 detection threshold). The magnitude and spread of SH were assessed using pinprick stimulation at nine time points up to 24 hours post-HFS. Temporal decay of HFS-induced increase in pinprick sensitivity was significantly slower in the HFS 2x5 versus the HFS 1x5 and HFS 1x10 groups (half-life: 438 vs. 255 vs. 247 min). In contrast, the time course of hyperalgesia area was similar in the HFS 2x5 and HFS 1x5 groups (451 and 470 min) but decayed more rapidly in the HFS 1x10 group (92 min). In the HFS 2x5 bilateral group, preexposure to HFS on one forearm did not affect contralateral hyperalgesia magnitude or half-life but slightly increased its spatial extent. These findings suggest that repeated exposure to noxious stimulation favors the induction of a longer-lasting form of central sensitization.